Analisis Determinan Produk Domestik Regional Bruto Sektor Pertanian Antar Wilayah di Kalimantan Selatan (Pendekatan Geographically Weighted Panel Regression) - Norarifin, Tri; Yanti, Nuri Dewi; Fauzi, Muhammad (Jurnal Sosial Ekonomi Pertanian, 2025)
The agricultural sector plays a strategic role in the Indonesian economy, including in South Kalimantan, but its contribution to the Regional Gross Domestic Product (GRDP) varies unevenly across regions. This study aims to analyze the determinants of the agricultural sector GRDP in South Kalimantan both globally and spatially. Using panel data from 13 regencies/cities for the period 2020–2024, the analysis was conducted using two approaches is global panel regression and Geographically Weighted Panel Regression (GWPR). The results show that the GWPR model is significantly superior in capturing spatial heterogeneity compared to the global model, with a Cross Validation (CV) value of 0.0425 and R² of 0.7042. At the local level, the GWPR model was able to explain up to 86.76% of the variation in Tabalong Regency. Globally, plantation area, capital expenditure (lag 1), and the mining sector's contribution significantly affect agricultural GRDP. However, GWPR estimates reveal substantial spatial variation, the coefficient of plantation area ranges from 0.036 to 0.233 (highest in Tabalong), capital expenditure from 0.019 to 0.050, while the mining sector's contribution shows a consistently negative effect (–0.035 to –0.006), with the strongest impact in mining-intensive areas. These findings confirm the necessity of differentiated policy approaches tailored to the local characteristics of each region.